Ansätze zur akustischen Optimierung von Reifen und Fahrbahnen für Elektrofahrzeuge unter Antriebsmoment - Stalter, Frank Christof (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
This work systematically describes the mechanisms of tyre/road noise atdriving and braking torque based on measurements with different tyres. The studies on the influence of circumferential force on tyre/road noise can be divided into two different tire tread designs. One sub-chapter reports about a selective influence of force induced tyre/road noise using inclined groove edges. The influence of the circumferential stiffness of the tread blocks on the tyre/road noise is discussed afterwards.